Stability of small-amplitude periodic solutions near Hopf bifurcations in time-delayed fully-connected PLL networks - Ferruzzo Correa, Diego P.; Bueno, Atila M. [UNESP]; Castilho Piqueira, Jose R. (Elsevier B.V., 2017)
In this paper we investigate stability conditions for small-amplitude periodic solutions emerging near symmetry-preserving Hopf bifurcations in a time-delayed fully-connected N-node PLL network. The study of this type of systems which includes the time delay between connections has attracted much attention among researchers mainly because the delayed coupling between nodes emerges almost naturally in mathematical modeling in many areas of science such as neurobiology, population dynamics, physiology and engineering. In a previous work it has been shown that symmetry breaking and symmetry preserving Hopf bifurcations can emerge in the parameter space. We analyze the stability along branches of periodic solutions near fully-synchronized Hopf bifurcations in the fixed-point space, based on the reduction of the infinite-dimensional space onto a twodimensional center manifold in normal form. Numerical results are also presented in order to confirm our analytical results. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Time-delay differential equations; Networks; Synchronization; Hopf bifurcation; Stability